Oxcarbazepine for refractory epilepsy: systematic review of the literature - Humberto Saconato; Gilmar Fernandes do Prado; Maria Eduarda dos Santos Puga; Álvaro Nagib Atallah (São Paulo Medical Journal)
CONTEXT AND OBJECTIVE: It has been estimated that 50 million people worldwide suffer from epilepsy and around 30% will not achieve adequate control over the disease. The aim was to evaluate the effectiveness of oxcarbazepine for refractory partial or generalized epilepsy. METHODS: Systematic review. A search was conducted in the PubMed, Lilacs, EMBASE and CENTRAL databases. Studies were analyzed using the Cochrane Collaboration methodology. RESULTS: Four randomized clinical trials of medium to poor methodological quality were included. Among the adult patients, the chances that they would obtain a 50% reduction in seizure frequency were greater after using oxcarbazepine at doses of 600 mg (relative risk, RR 2.11; 95% confidence interval, CI 1.32 to 3.35), 1,200 mg (RR 3.24; 95% CI 2.11 to 4.98) and 2,400 mg (RR 3.83; 95% CI 2.59 to 5.97). Among the children, the response in the group using oxcarbazepine was also greater (RR 2.11; 95% CI 1.32 to 3.35). The oxcarbazepine doses of 1,200 mg (RR 17.59; 95% CI 2.37 to 130.35) and 2,400 mg (RR 25.41; 95% CI 6.26 to 103.10) were effective for keeping patients probably free from seizures, but the dose of 600 mg was not. There was no significant difference between oxcarbazepine and carbamazepine for controlling the crises. CONCLUSIONS: There is moderate evidence indicating that oxcarbazepine is effective as an alternative treatment for partial or generalized epilepsy in children and adults who were refractory to previous treatment